2015
DOI: 10.1111/andr.12061
|View full text |Cite
|
Sign up to set email alerts
|

Decreased activity of superoxide dismutase in the seminal plasma of infertile men correlates with increased sperm deoxyribonucleic acid fragmentation during the first hours after sperm donation

Abstract: Sperm DNA fragmentation varies between individuals and is more pronounced with increased patient age and time after sperm donation. The intensification of DNA fragmentation depends on the balance of the oxidoreductive system, which is regulated mainly by two enzymes - superoxide dismutase (SOD) and catalase. The objective of this study was to determine the relationship between sperm DNA fragmentation dynamics, fertility and seminal SOD and catalase activity. The study was conducted in 2013 and 2014 at the Non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 39 publications
1
16
0
1
Order By: Relevance
“…Zelen et al () have reported a significant reduction of SOD and catalase activities along with increase in MDA content in seminal plasma of infertile men. Furthermore, a strong correlation was shown between the decreased activity of SOD and DNA fragmentation in the seminal plasma of infertile men (Wdowiak, Bakalczuk, & Bakalczuk, ). Alteration in testicular structure and functions in hypothyroid rats may then be due to the increase in MDA (marker of lipid peroxidation) along with the decrease in catalase and SOD activities reported in this work.…”
Section: Discussionmentioning
confidence: 99%
“…Zelen et al () have reported a significant reduction of SOD and catalase activities along with increase in MDA content in seminal plasma of infertile men. Furthermore, a strong correlation was shown between the decreased activity of SOD and DNA fragmentation in the seminal plasma of infertile men (Wdowiak, Bakalczuk, & Bakalczuk, ). Alteration in testicular structure and functions in hypothyroid rats may then be due to the increase in MDA (marker of lipid peroxidation) along with the decrease in catalase and SOD activities reported in this work.…”
Section: Discussionmentioning
confidence: 99%
“…DNA fragmentation was assessed using the sperm chromatin dispersion (SCD) test (Wdowiak et al, 2015) in four patients treated with the active drug, and in four treated with the control substance. Five of the 20 patients treated with the active drug fathered a child, whereas no control substance-treated patient fathered a child.…”
Section: Discussionmentioning
confidence: 99%
“…Five of the 20 patients treated with the active drug fathered a child, whereas no control substance-treated patient fathered a child. DNA fragmentation was assessed using the sperm chromatin dispersion (SCD) test (Wdowiak et al, 2015) in four patients treated with the active drug, and in four treated with the control substance. The SCD test data showed significant improvement in all the patients treated with Flortec (percentage of spermatozoa with fragmented DNA before Floretec administration: 45%, 39%, 44%, 65%; percentage of spermatozoa with fragmented DNA after Flortec administration: 22%, 25%, 20%, 21%), while the data did not significantly change in the patients who assumed the control substance (percentage of spermatozoa with fragmented DNA before starch administration: 49%, 48%, 62%, 58%; percentage of spermatozoa with fragmented DNA after starch administration: 41%, 45%, 66%, 55%).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an increasing interest has supervened regarding the types of fragmentations present in the DNA (Wei et al ., ) and how DNA fragmentation can be reduced in cryopreservation (Ghorbani et al ., ; Kably‐Ambe et al ., ; Simonenko et al ., ). Recent papers have shown a possible correlation between an increased amount of DNA fragmentation and some of the natural antioxidants present in the seminal plasma like superoxide dismutase (Wdowiak et al ., ) and glutathione peroxidase (Dorostghoal et al ., ).…”
Section: Historical Overviewmentioning
confidence: 99%